The Effect of Corporate Governance, Political Connection, and Executive Power on Corporate Social Responsibility Performance - Richo Diana Aviyanti; Nik Amah; Dwi Nila Andriani; Pramesti Widiastuti (Jurnal AKSI (Akuntansi dan Sistem Informasi), 2022)
CSR is a form of sustainability activity that must be a concern for the company because it poses a risk to existence. This study aims to determine the effect of governance, political connections, and executive power on CSR performance. The research uses a quantitative approach with a positivism paradigm. The research population is all issuers of the manufacturing sector listed on the Indonesia Stock Exchange during the 2017-2021 period. The research sample was 89 companies with 445 observations. Data were analyzed using multiple regression. The results show that corporate governance has a positive effect on CSR performance, whereas executive power has a negative effect on CSR performance. The political connection does not affect CSR performance. This research confirms stakeholder theory, legitimacy theory, and agency theory. The study results are also useful for investors/creditors in making investment decisions in companies, and top management can adopt CSR strategies that affect sustainability. This study uses a more comprehensive measurement variable.